Financial Literacy dan Niat Berinvestasi Bidang Properti pada Masyarakat Ekonomi Menengah - Ansori, Ansori; Qosim, Nanang; AR, Zaini Tamin (Proceedings of Annual Conference on Community Engagement, 2022)
Household finances, especially in the lower middle class economic strata, are objects that are vulnerable to financial and financial management problems that have an impact on the country's economy. So efforts to grow the community's economy require efforts to improve understanding of Financial literacy that can foster investment intentions, especially investment in businesses that have high growth such as property. This research takes the customer model at PT. Cipta Indo Buana, which is engaged in the property sector, applies a customer-to-customer marketing model, and makes each customer a marketing force by providing education about financial literacy. The results of this study indicate that the level of property sales in the form of raw land and plots increased rapidly in a period of three months and proves that increasing understanding of financial literacy in the middle to lower economic community is able to generate interest in investing in the community.